Perancangan Aplikasi Pelaporan Harian dengan Design Thinking dan User Experience Questionnaire (UEQ) - Triaji Morgana Kaban; Sarah Astiti; Dedy Agung Prabowo (JURIKOM (Jurnal Riset Komputer), 2023)
PT.TASPEN (Persero) is a State-Owned Enterprise (BUMN) assigned by the Government to administer social insurance and pension funds with the aim of improving the welfare of civil servants or participants and their families, both while still active and after retirement. In daily reporting activities at the PT TASPEN KC Purwokerto company, input will be made to the system during the activity. If the Prototype Design results are satisfactory, PT TASPEN KC Purwokerto employees can develop to the next stage, namely making the application and no longer need to use Microsoft Excel to report every day and of course it makes it very easy for users to input their daily reports into the application. The combination of these two methodologies helps in creating designs on the PT. TASPEN KC PURWOKERTO application that are of high quality and according to user needs. Problems that exist in the office of PT. TASPEN KC Purwokerto still uses Microsoft excel, the lack of supporting applications for daily reporting in fulfilling existing activities at the office of PT. TASPEN KC Purwokerto. The main purpose of this design is to simplify the daily reporting process for PT TASPEN KC Purwokerto employees and ensure that the daily reports are accurate and timely. Design Thinking is used to understand and meet the needs of PT TASPEN KC Purwokerto employees. The User Experience Questionnaire (UEQ) method contains 26 types of questions, where each question has a scale of 1 to 7. In terms of attractiveness, the average score obtained is 1.99 and get excellent category. Clarity gets an average score of 1.82 and is categorized as good. Efficiency gets an average score of 1.80 in the good category, accuracy gets a score of 1.75 in the excellent category, while stimulation gets a score of 1.90 in the excellent category, and lastly, novelty gets an average score of 1.84 in the excellent category. From the results of this assessment, it can be concluded that the design of the application is positively assessed by employees, because it has a pleasant, good, safe, comfortable, attractive design, and is easy for users to use. Based on these results, a daily reporting application system for employees of PT TASPEN KC Purwokerto will be designed and then an evaluation of the application system for daily employee performance reports will be carried out